Applying the Delphi technique to define 'medication wastage'. Issue 5 (19th March 2015) - West, Lorna Marie; Diack, Lesley; Cordina, Maria; Stewart, Derek
Abstract : Objective: The aim of this study was to apply the consensus-based Delphi technique to define 'medication wastage' and its contributory factors. Method: The Delphi technique was employed in this study, applying a minimum agreement consensus level of 75%. An expert panel comprising 26 professionals and six patients was recruited and communicated with by email. Round 1 comprised open-ended questions focusing on proposing a definition for 'medication wastage' and listing possible contributing factors. In round 2, respondents were requested to rank eight definitions of 'medication wastage', derived from round 1, in order of preference. Themes related to contributory factors were presented as 5-point Likert statements. Round 3 included statements that did not meet consensus in round 2. Results: Twenty-seven consented to participate, 23 of whom responded to both rounds. Of the eight options for defining 'medication wastage', the highest ranked was 'Medication wastage refers to any medication which expires or remains unused throughout the whole medicines supply chain. Also refers to the unnecessary or inappropriate consumption of medications by patients, or the unjustified non-adherence to treatment guidelines by healthcare professionals. Medication wastage poses a financial burden on patients themselves and the state's economy and requires adequate education of all people concerned'. Themes related to factors associated with wastage included physical/environmental, social/psychological (patient/practitioner) and cultural. Conclusions: A high level of consensus was achieved on a definition of medication wastage from a diverse panel of academics, practitioners, government officials, officials from non-governmental organisations, and patients in Malta.